2011
DOI: 10.1029/2011ja016934
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of MeV electrons at geosynchronous orbit during last two solar cycles

Abstract: [1] A comparison of MeV electron measurements at geosynchronous orbit, GEO, with solar wind shows that the MeV electron prediction model developed for GEO using data from the declining phase of solar cycle 22 (1995-1996) works well for the declining phase of solar cycle 23 (2006-2008), indicating that the MeV electron flux has a predictable and systematic response to the solar wind. The same comparison for solar maximum (2000)(2001)(2002)(2003) shows that the model works less well partly because it does not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 51 publications
(95 reference statements)
8
69
0
Order By: Relevance
“…SAMPEX revealed that the radiation belts change dramatically over multiple time scales for reasons that are not always readily apparent (Fig. 4;Baker et al 2004;Li et al 2011).…”
Section: Background and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…SAMPEX revealed that the radiation belts change dramatically over multiple time scales for reasons that are not always readily apparent (Fig. 4;Baker et al 2004;Li et al 2011).…”
Section: Background and Contextmentioning
confidence: 99%
“…Electron intensity (color scale) versus magnetospheric L-parameter (vertical axis) versus time (horizontal axis) for 2-6 MeV electrons as measured by the low altitude, polar orbit SAMPEX mission for over an entire ∼11-year solar cycle (Baker et al 2004; these measurements have continued for a second solar cycle; see Li et al 2011) In parallel with the new findings and interest in the radiation belts of Earth, extraterrestrial planetary probes have revealed robust radiation belts at all of strongly magnetized planets, despite the huge differences between the respective planets and despite the huge differences in how the space environments of these different planets are powered (Mauk and Fox 2010, and references therein). The creation of trapped populations of relativistic and penetrating charged particles is clearly a universal characteristic of strongly magnetized space environments and not just a characteristic of the special conditions that prevail at Earth.…”
Section: Figmentioning
confidence: 99%
“…[4] However, HSS events do not always lead to large flux enhancement [Kim et al, 2006;Li et al, 2011;Reeves et al, 2011], suggesting the involvement of other important solar wind parameters. Miyoshi and Kataoka [2008] conducted a superposed epoch analysis of MeV electrons at geosynchronous orbit about the 179 stream interface crossing events, which are precursor of the arrival of HSS events during solar cycle 23.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficiently convincing arguments for the mechanism of electron dropout at the magnetopause have been put forward in [Dmitriev, Chao, 2003;Shprits et al, 2006, Millan, Thorne, 2007Kim et al, 2008;Saito et al, 2010;Matsumura et al, 2011;Turner et al, 2012;Hudson et al, 2014;Lazutin, 2016]. In the quasitrapping region, drift shells are not closed; on the night side, electrons drift with adiabatic invariants remaining unchanged to the morning magnetosphere-magnetopause boundary; protons, to the evening boundary (and vice versa on the dayside); then they go from the closed field lines to the turbulent magnetosheath.…”
Section: Losses At the Magnetopausementioning
confidence: 99%
“…Figure 6 shows that RB gets rid of such an overpopulation for a long time. Note that strong storms may result in the formation of additional energetic electron belts in the vicinity of the slot region, which also exist for months [Vernov et al, 1965;Kuznetsov, 1966;Logachev, Lazutin, 2012].…”
Section: Acceleration Processes Slow E×b Driftmentioning
confidence: 99%